Spherical aberration of astigmatic corneas in a cataract population - Baur, Isabella; Auffarth, Gerd U.; Khoramnia, Ramin; Łabuz, Grzegorz (Journal of refractive surgery, 2023)
To study the distribution of spherical aberration (SA) in astigmatic corneas in a cataract population and the relationship between magnitude of corneal astigmatism and fourth-order corneal SA. -